2005
DOI: 10.1186/1475-2891-4-4
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional knowledge, food habits and health attitude of Chinese university students –a cross sectional study–

Abstract: Background: We have previously shown that irregular lifestyle of young Japanese female students are significantly related to their desire to be thinner. In the present study, we examined the nutritional knowledge and food habits of Chinese university students and compared them with those of other Asian populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
149
12
13

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(193 citation statements)
references
References 14 publications
19
149
12
13
Order By: Relevance
“…15,23,24 In contrast the prevalence of overweight and obesity among the Iranian male college students were only 7.9 % 25 and it was even low (2.9%) among the Chinese college students. 19 The prevalence rate of obesity in the current study is similar to the studies done by Majeed and Anding et al and it is slightly higher than the study done in Abha by Hakeem et al among the female college students. [26][27][28] Different studies across the globe reported various prevalence rate of overweight and obesity and that may be due to the differences in sample size and culture but still all the above described studies reveal that obesity and overweight are the major public health issue across the nation.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…15,23,24 In contrast the prevalence of overweight and obesity among the Iranian male college students were only 7.9 % 25 and it was even low (2.9%) among the Chinese college students. 19 The prevalence rate of obesity in the current study is similar to the studies done by Majeed and Anding et al and it is slightly higher than the study done in Abha by Hakeem et al among the female college students. [26][27][28] Different studies across the globe reported various prevalence rate of overweight and obesity and that may be due to the differences in sample size and culture but still all the above described studies reveal that obesity and overweight are the major public health issue across the nation.…”
Section: Discussionsupporting
confidence: 70%
“…The above mentioned habits are more or less similar with the student"s habit in Lebanon and china. 17,19 Majority of students in Kingdom of Saudi Arabia (45.17%) and in Lebanon (47.9%) have two times meals in a day whereas Majority of students in china has three times meals in a day. The current study shows that about 35% of the college students in the kingdom of Saudi Arabia eat snacks daily which are lower than in Lebanon where almost 50% of the college students eat snacks daily but in contrast only one tenth of the college students in china eat snacks daily.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most Saudi students (63·3 %) (19) eat irregular meals, whereas 64·6 % of Lebanese (51) and 81·6 % of Chinese (52) male university students take regular meals. The eating habits of the KSA youth population need to be improved using educational programmes aimed at promoting healthy eating habits.…”
Section: Discussionmentioning
confidence: 99%
“…As Instituições de Ensino Superior tornam-se importantes espaços para a aplicação de estratégias de promoção de estilos de vida saudáveis (Driskell, Kim, & Goebel, 2005;Lowry et al, 2000;Sakamaki, Toyama, Amamoto, Liu, & Shinfuku, 2005), implementando práticas de redução do excesso de peso e obesidade e manutenção de um peso adequado e capacitando os/as estudantes para a participação ativa e eficaz na construção de uma sociedade saudável (Precioso, 2004). Para além disso, não deve ser descurada a importância das cantinas e bares presentes nestes espaços que deverão ter uma responsabilidade acrescida, oferecendo ementas equilibradas, variadas e apelativas ao elevado número de estudantes que realizam refeições nesses locais.…”
Section: Procedimentosunclassified